Preliminary evaluation of alpha-emitting radioembolization in animal models of hepatocellular carcinoma - Du, Yong; Cortez, Angel; Josefsson, Anders; Zarisfi, Mohammadreza; Krimins, Rebecca; Liapi, Eleni; Nedrow, Jessie R. (PLOS ONE, 2022)
Hepatocellular carcinoma is the most common primary liver cancer and the fifth most frequently diagnosed cancer worldwide. Most patients with advanced disease are offered non-surgical palliative treatment options. This work explores the first alpha-particle emitting radioembolization for the treatment and monitoring of hepatic tumors. Furthermore, this works demonstrates the first in vivo simultaneous multiple-radionuclide SPECT-images of the complex decay chain of an [225Ac]Ac-labeled agent using a clinical SPECT system to monitor the temporal distribution. A DOTA chelator was modified with a lipophilic moiety and radiolabeled with the α-particle emitter Actinium-225. The resulting agent, [225Ac]Ac-DOTA-TDA, was emulsified in ethiodized oil and evaluated in vivo in mouse model and the VX2 rabbit technical model of liver cancer. SPECT imaging was performed to monitor distribution of the TAT agent and the free daughters. The [225Ac]Ac-DOTA-TDA emulsion was shown to retain within the HEP2G tumors and VX2 tumor, with minimal uptake within normal tissue. In the mouse model, significant improvements in overall survival were observed. SPECT-imaging was able to distinguish between the Actinium-225 agent (Francium-221) and the loss of the longer lived daughter, Bismuth-213. An α-particle emitting TARE agent is capable of targeting liver tumors with minimal accumulation in normal tissue, providing a potential therapeutic agent for the treatment of hepatocellular carcinoma as well as a variety of hepatic tumors. In addition, SPECT-imaging presented here supports the further development of imaging methodology and protocols that can be incorporated into the clinic to monitor Actinium-225-labeled agents.